Modulating photochemical reactions in Langmuir monolayers of Escherichia coli lipid extract with the binding mechanisms of eosin decyl ester and toluidine blue-O photosensitizers - Moreira, Lucas G. [UNESP]; Almeida, Alexandre M. [UNESP]; Nield, Tyler [UNESP]; Camacho, Sabrina A. [UNESP]; Aoki, Pedro H.B. [UNESP] (Elsevier, 2021)
Photodynamic damage to the cell envelope can inactivate microorganisms and may be applied to combat super-resistance phenomenon, empowered by the indiscriminate use of antibiotics. Efficiency in microbial inactivation is dependent on the incorporation of photosensitizers (PS) into the bacterial membranes to trigger oxidation reactions under illumination. Herein, Langmuir monolayers of Escherichia coli lipid extract were built to determine the binding mechanisms and oxidation outcomes induced by eosin decyl ester (EosDEC) and toluidine blue-O (TBO) PSs. Surface-pressure isotherms of the E. coli monolayers were expanded upon EosDEC and TBO, suggesting incorporation of both PSs. Fourier-transform infrared spectroscopy (FTIR) of Langmuir-Schaefer (LS) films reveled that the EosDEC and TBO binding mechanisms are dominated by electrostatic interactions with the anionic polar groups, with limited penetration into the chains. Light-irradiation reduced the relative area of E. coli monolayer on TBO, indicating an increased loss of material to the subphase owing to the chain cleavage, generated by contact-dependent reactions with excited states of TBO. In contrast, the increased relative area of E. coli monolayers containing EosDEC suggests lipid hydroperoxidation, which is PS contact-independent. Even considering a small chain penetration, the saturated EosDEC may have partitioned towards saturated reach domains, avoiding direct contact with membrane unsaturations.